The Relationship between Covid-19 Pandemic Anxiety and Expenditures for Postpartum Mother's Breastfeeding at the Air Joman Baru Sub-Health Center, Air Joman District, Asahan Regency Year 2021 - Herlia Suamrdha Nasution; Fithriani (Science Midwifery, 2022)
Many women of childbearing age (WUS) think that breast milk (ASI) is the best food for babies. The smoothness of breastfeeding is strongly influenced by psychological factors, one of which is anxiety due to the co-19 pandemic. This study aims to find out how the Anxiety of the Covid-19 Pandemic is related to the Expenditure of Breast Milk for Postpartum Mothers at the Air Joman Baru Sub-Health Center, Air Joman District, Asahan Regency in 2021. This research is a descriptive correlation study with a cross sectional approach. This research was carried out from 11 July 2021 to 24 July 2021. The population was 37 people. Sampling used total sampling with a total sample of 37 people, the research instrument used a questionnaire and data analysis with the chi-square test. The results of the study found that Covid-19 Pandemic Anxiety was in the anxious category, the majority of Postpartum Mothers' ASI expenditure was small. Based on the results of the chi-square test, it was found that there was a relationship between Covid-19 pandemic anxiety and breastfeeding for postpartum mothers at the Air Joman Baru Auxiliary Health Center, Air Joman District, Asahan Regency in 2021. The conclusion in this study is that there is a relationship between Covid-19 pandemic anxiety and postpartum mother's milk expenditure. Suggestions in this research are the Air Joman Baru Sub-district Health Center, Air Joman District, Asahan Regency, to conduct a psychological assessment of postpartum mothers during visits to the Health Center to maximize health services with special indicators for mother's milk production.